The Significance of Mentoring on Teachers Beliefs and Teachers Pedagogical Practices: A Comparative Analysis among 47 Countries Based on 2018 Teaching and Learning International Survey (TALIS) - Paul John Edrada Alegado; Hnin Yu Soe (University of Sofia, 2020)
The growing number of literature on mentorship suggests that mentoring influences teaching outcomes and student learning thereby improving the quality of education. However, to which elements mentoring have impacts on and the dispositions by which mentors and mentees develop remain unclear. This paper investigated the 2018 Teaching and Learning International Survey (TALIS) teacher questionnaire from lower secondary school teachers from a worldwide sample of 47 countries and proved statistically that mentoring has significant impact on teachers' pedagogical practices and teachers' beliefs. It also examined whether teachers' belief has significant influence on teachers' pedagogical practices. Drawing from previous studies, and two main conceptual models, this paper proposes a much clearer framework to better understand the dynamics of mentoring. The mentor-mentee relationship allows the transfer of different fundamentals and factors such as pedagogical, academic knowledge, psychosocial, attitudes, and behaviors throughout the mentoring process. This model accentuates the significance of an ongoing relationship between mentors and mentees that are reciprocally beneficial. Thus, when institutions design enabling environments that encourage and promote healthy and productive mentorship, this practice can play a key role in constantly nurturing professional knowledge, skills, and attitudes that the teaching force needs for them to educate and eloquently prepare their students more effectively.